The Native Language Transfer Into English Grammar By The Tenth Grade Students Of SMAN 1 Dolopo 1 Madiun In Writing Descriptive Text - Suryani, Ninik; , Agus Wijayanto, Ph.D; , Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
Based on the theory of transfer in the field of second language acquisition, in this research, the researcher found that the negative transfer of Indonesian is always done by the Indonesian students. This thesis tries to find an effective way to improve students' writing ability. Besides writing skills, native language transfer is one of the most important reasons for students' making errors in their writing. This study attempts to collect and analyze typical errors in compositions of descriptive text written by the tenth grade students of SMAN 1 Dolopo, Madiun. The data collection was done by giving test to students and the students are asked to write three times of task about writing descriptive text using their own sentences. The data collected were analyzed qualitative. The findings of the research, there are 813 Indonesian grammatical problems emerged from 2350 sentences of the students' English writing which are classified based on the surface strategy taxonomy proposed by Dulay et al. (1982); they are errors of omission, errors of addition, errors of misformation and errors of misordering. There are185 (22,8%) problems of omission "to be", 179 (22%) problems of omission -s/-es, and -d/-ed, 145 (17,5%) problems of direct translation, 90 (11,1%), problems of miss ordering of noun phrase, 61 (7,5%) problems of omission article "the", 54 (6,6%) problems of omission subject, 46 (5,7%) problems of omission main verb, 26 (3,2%) problems of misusing adverb of manner, 20 (2,5%) problems of idiosyncratic usage, and 7 (0,8%) problems of miss ordering adverb. The number of 185 (23%) about the omission of "to be", is the dominant emergence of Indonesian grammar into English grammar. An apparent feature in the learner's use of their interlanguage is simplification and overgeneralization. NL-based transfers were considered to be associated with both simplification and overgeneralization (Levenston, 1971; Varadi, 1973; Richards, 1974; Levenston & Blum-Kulka, 1977; Blum-Kulka & Levenston, 1983). Based on the findings, the researcher suggests that teaching English as a Second Language (ESL), at school must be given to the students when the students have mastered their native language grammatical system (Indonesian) well, before they are taught about English Grammatical system . Based on the research findings, some suggestions are given to the English teachers and the students. The teachers are suggested to give the students more exposures to the English structure that are different from those in Bahasa Indonesia and to pay attention on particular structures that often create difficulties for the students. The students are advised to expose themselves to many sources in English and more exercises especially in English structures that are considered difficult. Because of the students' best mastering of mother tongue, there will be positive transfer in studying English. Negative transfer of mother tongue will finally be overcome.